MASALAH NILAI EIGEN ATAS ALJABAR MAX-PLUS PADA SISTEM PRODUKSI BULU MATA - Novika, Nadya; Suroto; Guswanto, Bambang Hendriya (Universitas Insan Budi Utomo, 2023)
A discrete event system is a system whose behavior is determined by events and their events change at discrete times. The eyelash production system at PT Bio Takara Purwokerto is a discrete event system problem and can be expresses in a max-plus linear problem. By using the power algorithm, it is determined eigen values and eigen vectors over max-plus algebra which will be used as production time periodization. The results obtained that the periodic time for the eyelash production system at PT Bio Takara Purwokerto is 78.488 minutes. Based on this periodic time, we can then obtain the time each processing unit starts working to produce eyelashes.